2022
DOI: 10.1038/s41567-022-01558-3
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Dirac band curvature and momentum-dependent g factor in a kagome magnet

Abstract: The Zeeman effect describes the energy change of an atomic quantum state in magnetic field. The magnitude and the direction of this change depend on the dimensionless Landé g-factor. In quantum solids, the response of the Bloch electron states to the magnetic field also exhibits the Zeeman effect with an effective g-factor that was theoretically predicted to be dependent on the momentum. While typically negligible in many ordinary solids, the momentum-dependent variation of the g-factor is theorized to be subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Among these topological materials, magnetic Kagome materials are fascinating platforms to study the exotic physical properties due to their geometric frustration of crystal and magnetic structure [17], which is considered to be the root of many topological properties, like quantum spin liquid phase [18], flat band structure [19], Dirac or Weyl fermions [20][21][22], magnetic skyrmions [23], charge density wave [24][25][26] and so on. In Kagome materials, the SOC is also a key interaction to the topological properties [27,28], so they are ideal materials to study the influence of external magnetic field on electronic states, which has also been confirmed in some materials, like Fe 3 Sn 2 [29][30][31] and YMn 6 Sn 6 [32].…”
Section: Introductionmentioning
confidence: 86%
“…Among these topological materials, magnetic Kagome materials are fascinating platforms to study the exotic physical properties due to their geometric frustration of crystal and magnetic structure [17], which is considered to be the root of many topological properties, like quantum spin liquid phase [18], flat band structure [19], Dirac or Weyl fermions [20][21][22], magnetic skyrmions [23], charge density wave [24][25][26] and so on. In Kagome materials, the SOC is also a key interaction to the topological properties [27,28], so they are ideal materials to study the influence of external magnetic field on electronic states, which has also been confirmed in some materials, like Fe 3 Sn 2 [29][30][31] and YMn 6 Sn 6 [32].…”
Section: Introductionmentioning
confidence: 86%
“…In an inplane magnetic field, the continuously varying spin structures may change the Fermi surface topology, causing a Lifshitz transition and a sharp reduction of the magnetoresistance up to 45% [148]. Under an out-of-plane magnetic field, STM experiments have also identified the manipulation of the massive Dirac cone near the Fermi level in YMn 6 Sn 6 [145]. By subtracting the band dispersions from quasiparticle interference (QPI) data, it was found that in addition to an overall Zeeman shift of the massive Dirac cone with increasing field, the band bottom of the Dirac cone is significantly rounded (figure 5(d)) due to a momentum-dependent g factor peaking around the Dirac point (figure 5(e)).…”
Section: Topological Band Engineeringmentioning
confidence: 99%
“…By subtracting the band dispersions from quasiparticle interference (QPI) data, it was found that in addition to an overall Zeeman shift of the massive Dirac cone with increasing field, the band bottom of the Dirac cone is significantly rounded (figure 5(d)) due to a momentum-dependent g factor peaking around the Dirac point (figure 5(e)). Several mechanisms have been proposed to explain this evolving factor, including the large orbital magnetic moments primarily localized near the Dirac points, the spin canting induced Dirac gap enhancing, as well as the evolving magnetic exchange coupling [145].…”
Section: Topological Band Engineeringmentioning
confidence: 99%
“…Spectral peaks in STM dI/dV spectra of related materials have been typically associated with either Landau levels [35][36][37] , flat bands 28,38 , massive Dirac fermions 21 , and/or saddle points 39 . We deem that these are unlikely to explain the emergence and the evolution of spectral features in our work for the following reasons.…”
Section: Magnetization-direction-driven Tunability Of Di/dv Featuresmentioning
confidence: 99%